Boys will be superintendents: School leadership as a gendered profession. (October 2018) - Maranto, Robert; Carroll, Kristen; Cheng, Albert; Teodoro, Manuel P.
Even though the teaching profession is dominated by women, men hold more superintendent positions. The authors examine the pipeline that leads to the principalship and the superintendency and how it has evolved over time. They note school boards are more likely to perceive high school principals and athletic coaches as plausible superintendents, in contrast to elementary principals and curriculum specialists. In addition, elementary education majors, mostly women, tend to be more conservative and thus may choose family over advancement to a more demanding position. They discuss why having more women in high-level leadership is valuable and ways to reform the gendered career track .